2017
DOI: 10.1002/cctc.201700108
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Isopropyl Ethers: Direct Synthesis from Alcohols and Synthesis by the Reduction of Solketal

Abstract: The catalytic reduction of solketal ((2,2‐dimethyl‐1,3‐dioxolan‐4‐yl)methanol) over bifunctional heterogeneous palladium catalysts is proposed as an alternative to the synthesis of glycerol isopropyl ethers by the etherification of glycerol. The direct synthesis of glycerol isopropyl ethers from isopropanol and glycerol requires severe conditions (T=130–150 °C, p(H2)=20–35 bar) and a large excess of isopropanol to reach a considerable yield. The main reaction products in the catalytic reduction of solketal are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 61 publications
(153 reference statements)
1
21
0
Order By: Relevance
“…In the comparison of three mesoporous aluminosilicas (Al‐HMS) with various Si/Al ratio the most Al‐rich material (Al‐HMS(10)) was less active, whereas on going to Al‐HMS(40) the activity has increased. This correlation is quite typical for reactions where glycerol is alkylated (or acetalised),,, but surprisingly K‐10 was far more active that zeolite BEA‐40. To all appearances, since no water is liberated in the transacetalization reaction, the hydrophobicity of the aluminosilica catalyst exerts the reversed influence.…”
Section: Resultsmentioning
confidence: 73%
“…In the comparison of three mesoporous aluminosilicas (Al‐HMS) with various Si/Al ratio the most Al‐rich material (Al‐HMS(10)) was less active, whereas on going to Al‐HMS(40) the activity has increased. This correlation is quite typical for reactions where glycerol is alkylated (or acetalised),,, but surprisingly K‐10 was far more active that zeolite BEA‐40. To all appearances, since no water is liberated in the transacetalization reaction, the hydrophobicity of the aluminosilica catalyst exerts the reversed influence.…”
Section: Resultsmentioning
confidence: 73%
“…The acidity of the mesoporous aluminosilicas demonstrates a non-linear growth with the increase in the Al content. The acidity strength distribution pattern for Al-HMS aluminosilicas determined previously has shown that strong acid sites are practically absent, what might provide the high selectivity in the reaction of the cyclic ketals hydrogenolysis [39].…”
Section: The Glycol Ethers Synthesis Via the Hydrogenolysis Of The Comentioning
confidence: 85%
“…The properties of the catalysts used for 1,2-PD and 2,3-BD monoether synthesis are given in Table 3. The performance of Pd/Al-HMS materials in the cyclic glycerol ketal hydrogenolysis reaction and the characterization details have been previously reported [39], so in this paper only the brief description is given. The values of the specific surface areas for the catalysts indicate well-developed pore structures (between 680 m 2 g −1 and 850 m 2 g −1 ) and a narrow pore size distribution with mean pore sizes of about 3-5 nm.…”
Section: The Glycol Ethers Synthesis Via the Hydrogenolysis Of The Comentioning
confidence: 99%
See 1 more Smart Citation
“…Among many, hydrogenation/hydrogenolysis [8,9] and transfer hydrogenolysis [10][11][12] of cellulose, hemicellulose, lignin, C6-C3 polyols, furan derivatives and aromatic ethers represent a core technology of modern biorefineries. Glycerol (C3 polyol) and glycidol (2,3-epoxy-1-propanol) can be converted into hydrogen (via APR process), C3-C1 alcohols, as well as to cyclic acetals and ketals [13][14][15][16]. Accordingly, reforming processes are surely a new way for the production of H 2 and liquid hydrocarbons from lignocellulosic biomasses or their derived molecules [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%